Perlindungan Hukum Konsumen dalam Transaksi Digital: Tantangan dan Upaya Hukum berdasarkan Undang-Undang Nomor 8 Tahun 1999 (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2026)
The development of electronic commerce (e-commerce) in Indonesia has grown rapidly alongside the increased use of digital technology by the public. While offering convenience and efficiency in transactions, e-commerce also presents various legal challenges that may harm consumers, such as unclear product information, personal data breaches, and weak dispute resolution mechanisms. These conditions highlight the importance of consumer legal protection in digital transactions. This study aims to analyze consumer legal protection in e-commerce transactions, focusing on existing challenges and legal remedies based on Law Number 8 of 1999 concerning Consumer Protection and Government Regulation Number 80 of 2019 on Trade Through Electronic Systems. The research employs a qualitative method with a normative juridical approach. Data were collected through literature review of primary legal materials, including laws and regulations, as well as secondary materials such as journals, books, articles, and other relevant sources. The findings indicate that consumer legal protection in Indonesian e-commerce transactions has an adequate legal foundation. Law Number 8 of 1999 serves as the main basis for protecting consumer rights, while Government Regulation Number 80 of 2019 strengthens regulations in response to digital commerce developments. However, implementation remains challenging, particularly regarding supervision and consistent law enforcement. Therefore, stronger government involvement, increased responsibility of e-commerce businesses, and improved consumer awareness are needed to achieve effective and sustainable consumer protection.